IMPLEMENTASI PSYCHOLOGY FACTORS, RISK PERCEPTION, SOCIAL MEDIA SENTIMENT DAN HERDING BEHAVIOR TERHADAP KEPUTUSAN INVESTASI (STUDI PADA INVESTOR SAHAM MAHASISWA UNIVERSITAS LAMPUNG): IMPLEMENTASI PSYCHOLOGY FACTORS, RISK PERCEPTION, SOCIAL MEDIA SENTIMENT DAN HERDING BEHAVIOR TERHADAP KEPUTUSAN INVESTASI (STUDI PADA INVESTOR SAHAM MAHASISWA UNIVERSITAS LAMPUNG) - Syafitri, Rahmadia Utami; suripto, suripto (Jurnal Kompetitif Bisnis, 2023)
There are many things that underlie an investment decision such as the rational and irrational attitude of an investor. This study aims to find out the important role played by psychology factors, risk perception, social media sentiment, and herding behavior in influencing investment decisions in Lampung University student investors. The type of explantory research with a research approach is quantitative. The method used in this study is a quantitative research method. The population in this study is all active students of the University of Lampung for the 2022/2023 period using a sampling technique, namely purposive sampling with a sample of 100 respondents. The data was obtained from the questionnaire using a likert scale. Data analysis of this study used multiple regression analysis. The results obtained from this study partially show that psychology factors, risk perception, social media sentiment, and herding behavior have a significant effect on investment decisions. The results of simultaneous testing of psychology factors, risk perception, social media sentiment, and herding behavior on investment decisions.